2001
DOI: 10.1046/j.1439-0507.2001.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report. Lymphatic vessel-type sporotrichosis: immunohistochemical evaluation and cytokine expression pattern

Abstract: A 57-year-old male carpenter living in Sagamihara, Kanagawa Prefecture, visited the Department of Dermatology of Kitasato University Hospital because an ulcer which appeared in his left forearm around May 1992 had spread gradually. An oval, shallow ulcer measuring 39 mm x 18 mm was found on the flexor aspect of the left forearm. Histopathological examination showed partial ulceration on the epidermis and marked cell infiltration throughout the entire dermal layer with an abscess in the centre and granulomatous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Administration of terbinafine at a dose of 250 mg was chosen based on in vitro studies demonstrating an excellent sensitivity profile of S. schenckii , as well as on clinical reports showing successful treatment of cutaneous sporotrichosis with this dose 8–11 . Terbinafine has shown low minimum inhibitory concentrations (0.007–0.5 µg/mL) against the fungus in in vitro studies, and some investigators reported terbinafine to be the most active drugs among other antifungal agents tested, including itraconazole and amphotericin B 15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of terbinafine at a dose of 250 mg was chosen based on in vitro studies demonstrating an excellent sensitivity profile of S. schenckii , as well as on clinical reports showing successful treatment of cutaneous sporotrichosis with this dose 8–11 . Terbinafine has shown low minimum inhibitory concentrations (0.007–0.5 µg/mL) against the fungus in in vitro studies, and some investigators reported terbinafine to be the most active drugs among other antifungal agents tested, including itraconazole and amphotericin B 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Binding of the drug to microsomal cytochrome P450 enzymes is low (approximately 5% of total capacity), thus not affecting the bioavailability of other drugs metabolized by this enzyme system 6 . Clinical trials and case reports 7–11 investigating the use of terbinafine for sporotrichosis treatment, with doses ranging from 125 mg to 1 g/day, suggested that the drug is safe and effective in the treatment of cutaneous sporotrichosis. However, there is no consensus regarding the optimal regimen and duration of terbinafine treatment in sporotrichosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although MIF involvement has been suggested in fungal infections (Defaveri et al 1992;Farah et al 2001;Golec et al 2004;Graybill et al 1983;Krysińska-Traczyk and Dutkiewicz 2000;Nicolo et al 2006;Singh et al 1990;Tanuma et al 2001;Tewari and Von Behren 2000;Vorob ev et al 1983), its exact role in the host control of infection is not well known. To determine the possible relevance of MIF in host defense against A. fumigatus we have conducted experiments using a model of systemic aspergillosis (Cenci et al 1997;Clemons et al 2010;Mirkov et al 2011), induced in MIF-deficient mice generated on the relatively resistant C57BL/6 background (Cenci et al 1997;Mirkov et al 2010;Zaas et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Data from experimental animal infection models have demonstrated involvement of MIF in fungal infections as well, including those caused by the respiratory fungus, Histoplasma capsulatum (Tewari and Von Behren 2000), Paracoccidioides brasiliensis (Defaveri et al 1992) and the opportunistic fungi, Candida albicans (Farah et al 2001;Nicolo et al 2006;Vorob ev et al 1983) and Cryptococcus neoformans (Graybill et al 1983). Involvement of MIF was noted in human candidiasis (Singh et al 1990) and sporotrichosis (Tanuma et al 2001). With the exception of data showing strong potential of Aspergillus candidus antigens in inducing MIF activity in rabbits (Krysińska-Traczyk and Dutkiewicz 2000) and increased MIF activity in workers professionally exposed to herbal dusts containing A. fumigatus (Golec et al 2004), there are no data concerning the relevance of MIF in infections caused by fungi of the genus Aspergillus.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few reports of the successful use of terbinafine in patients with cutaneous sporotrichosis; [14][15][16] however, the available data are scarce, and further trials are needed to define the role of terbinafine in the treatment of sporotrichosis.…”
Section: Discussionmentioning
confidence: 99%